A new zinc complex based on 5-bromoisophthalic acid and 1, 2-bis(imidazole-1-yl)ethane: Hydrothermal synthesis, crystal structure, and properties. Issue 8 (3rd August 2017) - Zhao, En-Xiao; Li, Fei-Fei; Shi, Zhen-Zhen; Zhang, Rong-Hua; Zhao, Dan
ABSTRACT: A new complex, [Zn(5-Br-ip)(1, 2-Bie)]n (1 ), (5-Br-ipH2 = 5-bromoisophthalic acid; 1, 2-Bie = 1, 2-bis(imidazole)ethane), has been synthesized by hydrothermal reaction. Its crystal structure was characterized by single-crystal X-ray diffraction analysis and IR spectroscopy. The X-ray single-crystal structure shows that complex1 belongs to the monoclinic system, C 2/ c space group, a = 22.367(3), b = 8.2224(12), c = 18.615(4) Å, β = 126.21(0)°. The complex exhibits a complicated (3, 4)-connected 3D 3-fold interpenetrating network with a Schläfli symbol of (4 2 ·6·10 2 ·12)(4 2 ·6) topology. The adjacent Zn ions were constructed of one-dimensional double chains, having dinuclear [Zn(COO)2 ] units bridged by 5-Br-ip. Fluorescence measurements show that the complex has fluorescent emissions at 419 nm upon excitation at 361 nm.